Perception of Faculty teachers towards OSCE in Public Nursing Colleges of Peshawar: Perception of Faculty teachers towards OSCE - Khan, Sheraz; Naz, Najma; Khaum , Sabiha; Zabeeda , Malika; Siddique , Usama; Salman, Muhammad (Pakistan Journal of Health Sciences, 2022)
There are different methods of evaluating clinical competencies in medical field students, among which the objective structured clinical examination is considered the most reliable and effective way of assessing clinical skills. Most popular method for assessment of clinical skills in Nursing Education. Objective: The study aims to explore and compare the perceptions of nursing faculty members regarding objective structured clinical examination application in the evaluation and assessment of the clinical skills of the nursing students. Methods: A descriptive cross-sectional design was used to collect data from 46 Faculty teachers through simple random sampling. Content validity of the adopted questionnaire was verified by (5) experts in the field of nursing education and the internal consistency of the scale was found to be excellent (Cronbach’s Alpha =0.949). Results: The mean age of study participants was 38.23±9.69. The majority of Participants 82.6 % (n=38) were females Half of the participants were Post RN BSN in qualification (n=23). Perceptions were categorized into positive and negative by the median cut-off value. 93.5 % faculty teacher’s express positive attitude regarding training and conducting of Objective Structured Clinical Examination. Conclusions: The study concluded that, the faculty teacher’s knowledge skills and attitude were positive regarding the Objective Structured Clinical Examination (OSCE) exam. The study revealed that OSCE is an appreciated practical learning experience and maximum of the faculty teachers agreed that OSCE facilitated the assessment and develop their psychomotor skills. P=0.05 so there is no association found between age group, gender, level of education and perception